Monitoreo remoto con red de sensores, para el sistema de calentamiento por colectores solares de la piscina del TEC - Espinoza-Ortiz, Luis Carlos (Instituto Tecnológico de Costa Rica, 2018)
This document contain steps to develop a sensor network monitor system applied to the heat up pool system through solar thermal collector. The steps began with sensor's characterization to design a signal conditioner that allow the microcontroller capture the data from the sensor. This will be packet so it can be transmitted using radio-frequency in a wireless way to the main node that it takes data and contrast it with a dynamic model which calculate a theorical temperature from the pipes and can be compare it with the information captured from the sensor. This data will be transmitted through Wi-Fi to a server.
Proyecto de Graduación (Licenciatura en Ingeniería Electrónica) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electrónica, 2018
Keywords: Radiofrecuencia; Temperatura; Radiación; Research Subject Categories::TECHNOLOGY::Electrical engineering, electronics and photonics::Electronics